A Contextual Analysis of the Late Roman Pewsey and Wilcot Vessel Hoards, Wiltshire. (November 2019) - Henry, Richard; Roberts, David; Grant, Michael J.; Pelling, Ruth; Marshall, Peter
Abstract: In late summer, sometime between cala.d . 340–405, a hoard of tightly packed, stacked copper-alloy vessels was deposited in the Vale of Pewsey, Wiltshire. The corrosion of the vessels allowed for the preservation of delicate plant macrofossils and pollen. Analysis of this material has provided insights into the date, season and context of this act of structured deposition. A second hoard of similar vessels was deposited in the fourth or fifth century only a few miles away at Wilcot. The hoards and their deposition relate to Romano-British lifeways, at a time when the region was on the cusp of a dramatic period of change. The distribution of late Roman coins and belt fittings offers further insights into the social and economic character of Wiltshire at their times of deposition.